The effectiveness of the ethanol extracts of avocado leaves larvicide against Aedes aegypti and Culex quinquefasciatus larvae mortality - Dina Mellina Putri; M Ali S; Supriatno Supriatno (Jurnal Edubio Tropika, 2018)
This research aims to find out the influence of the ethanol extracts of avocado leaves against larvae mortality of Aedes aegypti. This research was carried out in July 2014 until June 2015. The method usedis Complete Random design experiment method consists of seven treatments and four replicates.Concentrations of ethanol extract of the leaves of the avocado are 1000 ppm, 2000 ppm, 3000 and 4000 ppm,ppm 5000 ppm. Analysis of the influence of the ethanol extracts of avocado leaves against mortality of larvae is performed with ANOVA test, while the LC50 is performed with probit test. ANOVA test results of Aedesaegypti larvae mortality obtained a value of Fcount = 1597.72 Ftable(0.05) = 2.57 and Culex quinquefasciatus larvae mortality retrieved the value Fhitung = 1127.19 Ftabel(0.05) = 2.57. The result of LC50 analyzes at 72 hours observation showed the concentration of ethanol extract of avocado leaves that can kill 50% Aedes aegyptilarvae is 732,84 ppm and Culex quinquefasciatus larvae is 961,75 ppm. The conclusion obtained is the administering of ethanol extracts of avocado leaves significantly affect the mortality of the larvae of Aedesaegypti and Culex quinquefasciatus, thus it is potential to be used as natural larvicide.Keywords: Larvicide, Avocado leaves, Aedes aegypti and Culex quinquefasciatus